EOLES course - Gericota, Manuel G. (2015)
The EOLES course is the main result of an innovative and groundbreaking TEMPUS project, focused in Engineering Education. It covers all the problematic areas of Engineering Education, trying of find a suitable compromise in satisfying all the methods of evaluating engineering degrees. EOLES is an international cooperative project, with an emphasis not only on one of the facets of engineering education, but trying to involve all of them. This paper describes the course’s preparation and accreditation, its structure (motivated by pedagogical constraints), the E-learning framework, and the virtual and remote laboratories and their integration in the course. Some data related to the current first edition of the course are provided, namely the number of applicants and their countries of origin. While limited to a 3rd year in a Bachelor’s Degree, for now, it is expected to be extended to a full course in a near future. The EOLES course is the result of an international effort involving experts from different engineering and education areas, in order to provide a better global Engineering Education.